Identification of a putative monolignol transporter gene homolog III in Oryza sativa - Azhar, Aidil Hakim (2015)
Lignin is important to plant cell as it gives a strong structure and protects the plants from biotic and abiotic stresses. Lignin is made up from monomers called monolignols. There are three types of monolignols which are p-coumaryl alcohol, coniferyl alcohol and sinapyl alcohol. Monolignols are synthesized in the cytoplasm of the cell. These monolignols will be transported through the plasma membrane and polymerized at the cell wall of the plant. The mechanism of monolignol transport is still unclear. One previous study has shown that AtABCG29 is involved in transporting p-coumaryl alcohol across plasma membrane in Arabidopsis thaliana. AtABCG29 gene encodes for protein that is localized at the plasma membrane and is called monolignol transporter. The aim of this study is to identify the gene that encodes for the protein that is involved in transporting monolignol across the plasma membrane in Oryza sativa. The gene of hypothetical protein OsI_23352 from Oryza sativa has shown to has a high percentage of identity and homologous to AtABCG29 in Arabidopsis thaliana. Therefore it was chosen as candidate to find the monolignol transporter gene homolog III in Oryza sativa.